Neuropsychological assessment of diverse populations in Europe: The European Consortium for Cross‐Cultural Neuropsychology (ECCroN). (December 2021) - Franzen, Sanne; Mukadam, Naaheed; Calia, Clara; Watermeyer, Tam J; Canevelli, Marco; Pomati, Simone; Goudsmit, Miriam; van den Berg, Esther; Papma, Janne M; Ibanez‐Casas, Inmaculada; Lozano‐Ruiz, Alvaro; Fasfous, Ahmed; et al.
Abstract: Background: Populations living in European countries are becoming increasingly diverse. As performance on traditional neuropsychological tests is heavily influenced by culture, language, (level and quality of) education, literacy, and other factors, neuropsychological assessment practices need to be adapted to account for this diversity. Method: The European Consortium for Cross‐Cultural Neuropsychology (ECCroN) aims to improve assessment of culturally, educationally, and linguistically diverse individuals across Europe by 1) collaborating on the validation and implementation of cross‐cultural neuropsychological tests and 2) working on initiatives geared at improving interpreter use and training programs for neuropsychologists. Result: The consortium was founded in late 2019 and currently consists of 16 experts based in 9 countries – some of whom work in multinational contexts. The first meetings of the network stressed several points. First, ECCroN aims to develop and/or validate cross‐culturally applicable tests, as opposed to race‐based norms for existing tests; for example, current projects aim to validate measures of social cognition and language (naming) in patients with migration backgrounds. Second, ECCroN emphasizes the importance of taking into account diversity across the entire spectrum, both in populations traditionally considered to be 'majority' and 'minority' groups, e.g. best practices should be developed for those with little education regardless of native‐born or migrant status. Third, ECCroN aims to identify and share suitable instruments to measure factors potentially influencing the assessment, such as bilingualism, acculturation and educational quality. Conclusion: Joint efforts should be undertaken to develop, validate, publish, and implement cross‐cultural tests across European countries to reduce misdiagnoses in diverse patient populations.